A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 4 - It is essential to any comprehensive service on national lines that there should be a general right of ultimate reference from the periphery to the centre. In other words, the Local Hospitals Council, and severally the Joint Authority and the voluntary hospitals represented thereon, shouId enjoy the right to refer to the Central Hospitals Board matters in dispute unresolved in the Regional Hospitals Council. 8. - Purpose of Separate Hospital Structure. It may be appropriate to give some explanation of the reasons why the voluntary hospitals regard the setting-up of the hospital board and councils as of such paramount importance. The history and experience of the voluntary hospitals, as institutions for the care and healing of the sick, is centuries older than that of the local authority hospitals. Their record of service is incomparably more impressive and their standards, with a few exceptions, inmeasurably higher. In research they stand alone. Their contribution of effective hospital beds to a comprehensive service will be substantially greater and more widely spread than the contribution of the local authorities. A Comprehensive Health Service must be designed in the interests of the patient. The voluntary hospitals do not seek a continued existence for any other reasons than that their freedom from regimentation and standardisation is in the interests of the patient because it provides an essential element in the maintenance and improvement of the highest standards of treatment. Further, the voluntary hospitals do provide to the patient unrestricted freedom in his choice of hospital, subject only to the necessary facilities being available and adequate at the hospital selected. The White Paper has conceded this freedom in respect of choice of doctor and the voluntary hospitals attach the greatest importance to the patient continuing to have freedom to choose his hospital. An administrative structure without the hospitals board and councils above mentioned would pass the whole of the control of the hospital services of the country into the hands of the major local authorities. Not only would the local authorities control the hospital services, but as owners of the municipal hospitals there would inevitably be a tendency for the control to function more favourably to the municipal hospital than to the voluntary hospital. This could have no other result, for the reasons above mentioned, than a lowering of the standards of hospital service and consequently of medical practice. It must be the aim of all to produce the best possible hospital service available. Failure to do this would mean failure in duty to the patient, and the voluntary hospitals themselves would be failing in their trust if they submitted to a scheme in which they could not play a full and adequate part. * It may be held that it would be most desirable that the plan should be sent direct by the Local Hospitals Council to the Regional Hospitals Council. 9. - Implications of the Government's Administrative Proposals. It is of vital importance that the full implications of the proposed administrative structure should be realised, not only by parliament, but by the community whom it is the privilege of the voluntary hospitals to serve. Indeed, if it were the intention of the government to destroy the voluntary hospitals, no surer method could have been devised than an administrative structure as set out, which places them in a position of complete subservience to the local authorities, gives them no representation on the Joint Authority, and gives them no effective voice in the planning of the hospital service, nationally or locally. (contd.) 292/847/2/33